X-ray spectroscopic investigation of crystal fields in Ce2⁢Rh1−𝑥⁢Ir𝑥⁢In8 heavy fermions - Sacramento Christovam, Denise; Marino, A.; Falke, J.; Liu, C.-E.; Chang, C.-F.; Kuo, C.-Y.; Stockert, O.; Wirth, S.; Haverkort, Maurits W.; Zwicknagl, G.; Severing, A.; Rosa, P. F. S.; et al. (Physical review, 2024)
The higher dimensionality in the crystal fields of the Ce2⁢𝑀⁢In8 (𝑀=Rh,Ir) compounds and its interplay with hybridization and disorder are key ingredients to understand the complex phase diagrams by this family, which have been explored extensively by macroscopic techniques. Here, we present an investigation of the crystal-electric field schemes of Ce2⁢Rh1−𝑥⁢Ir𝑥⁢In8 using x-ray absorption spectroscopy. Our full multiplet calculations for the 4⁢𝑓1 configuration of Ce3+ to describe the temperature-dependent linear dichroism in Ce2⁢𝑀⁢In8 are consistent with a Γ17=√1−𝛼2·|∓32⟩−|𝛼|·|±52⟩ ground state containing a predominant |±3/2⟩ contribution that increases further with 𝑥. This enhancement is believed to favor superconductivity in Ce-based heavy fermion materials, observed in previous results in the Ce⁢𝑀⁢In5 family. Our recent observations shed light on the unexpected emergence of the ambient-pressure superconducting dome in the center of the composition phase diagram and its subsequent suppression on the Ir-rich side due to the early onset of fluctuations associated with the structurally more disordered state, inferred from previous neutron magnetic diffraction experiments.